Pattumateang among Peoples of Cikoang, South Sulawesi: A Local Practice of Mortuary Ritual in the Islamic Community - Muhammad Adlin Sila (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2008)
Pattumateang, conducted after the burial service, is conceived as a means through which the living can transfer blessings to the dead. This practice has been the cause for an everlasting debate among Muslims in Cikoang. Some object to the concept of being able to help the dead and call on followers to accept proper Islamic teachings and practices. This article is an illustration of how the Pattumateang ritual, and others like it, can lead to the creation of two opposing groups of Muslims, those for and against such a ritual.DOI: 10.15408/sdi.v15i2.532